2021
DOI: 10.1016/j.xcrm.2021.100343
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic profiling reveals distinct mechanical responses between normal and diseased tendon progenitor cells

Abstract: Regenerative medicine approaches utilizing stem cells offer a promising strategy to address tendinopathy, a class of common tendon disorders associated with pain and impaired function. Tendon progenitor cells (TPCs) are important in healing and maintaining tendon tissues. Here we provide a comprehensive single cell transcriptomic profiling of TPCs from three normal and three clinically classified tendinopathy samples in response to mechanical stimuli. Analysis reveals seven distinct TPC subpopulations includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…In vitro POSTN_KRT7, PTX3_PAPPA, ITGA7_ NES and DCN_LUM clusters showed increased expression of the top differentially expressed genes initially found in the ex vivo POSTN+, PTX3+, ITGA7+ and APOD+ clusters, respectively. This supported the possibility that human tendon cell clusters represented populations that can be isolated ex vivo and remain discrete subtypes in vitro (Still et al, 2021). There was little in the gene expression profile of cultured DKK1_FGF5 and PRELP_FMOD to relate them to cell clusters found in the ex vivo atlas.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…In vitro POSTN_KRT7, PTX3_PAPPA, ITGA7_ NES and DCN_LUM clusters showed increased expression of the top differentially expressed genes initially found in the ex vivo POSTN+, PTX3+, ITGA7+ and APOD+ clusters, respectively. This supported the possibility that human tendon cell clusters represented populations that can be isolated ex vivo and remain discrete subtypes in vitro (Still et al, 2021). There was little in the gene expression profile of cultured DKK1_FGF5 and PRELP_FMOD to relate them to cell clusters found in the ex vivo atlas.…”
Section: Discussionmentioning
confidence: 75%
“…These results suggested that aligned electrospun PDO fibres provided a useful scaffold and environment for their ongoing investigation in vitro. A similar population of cells expressing IL8, CXCL1/6/8 and PTX3 was described in single-cell transcriptomics of healthy and diseased patellar tendon progenitor cells cultured under mechanical stress (Still et al, 2021). Most of these named "pro-inflammatory tendon progenitor cells" were from diseased human tendon and expressed gene sets enriched for pro-inflammatory signalling pathways, including the "IL-1 regulation of extracellular matrix" category.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations